Interaction of vanadate with the cloned beta cell K(ATP) channel. - Proks, P; Ashfield, R; Ashcroft, F (1999)
Vanadate is used as a tool to trap magnesium nucleotides in the catalytic site of ATPases. However, it has also been reported to activate ATP-sensitive potassium (K(ATP)) channels in the absence of nucleotides. K(ATP) channels comprise Kir6.2 and sulfonylurea receptor subunits (SUR1 in pancreatic beta cells, SUR2A in cardiac and skeletal muscle, and SUR2B in smooth muscle). We explored the effect of vanadate (2 mM), in the absence and presence of magnesium nucleotides, on different types of cloned K(ATP) channels expressed in Xenopus oocytes. Currents were recorded from inside-out patches. Vanadate inhibited Kir6.2/SUR1 currents by approximately 50% but rapidly activated Kir6.2/SUR2A ( approximately 4-fold) and Kir6. 2/SUR2B ( approximately 2-fold) currents. Mutations in SUR that abolish channel activation by magnesium nucleotides did not prevent the effects of vanadate. Studies with chimeric SUR indicate that the first six transmembrane domains account for the difference in both the kinetics and the vanadate response of Kir6.2/SUR1 and Kir6. 2/SUR2A. Boiling the vanadate solution, which removes the decavanadate polymers, largely abolished both stimulatory and inhibitory actions of vanadate. Our results demonstrate that decavanadate modulates K(ATP) channel activity via the SUR subunit, that this modulation varies with the type of SUR, that it differs from that produced by magnesium nucleotides, and that it involves transmembrane domains 1-6 of SUR.